2017
DOI: 10.1111/inm.12334
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and correlates of benzodiazepine use in nurses: A nationwide, population‐based study

Abstract: ABSTRACT:In the present study, we examined patterns of benzodiazepine (BZD) use in nurses, and compared the characteristics of frequent users with those of infrequent users. Data on all nurses enrolled in the study were derived from the reimbursement claim records in Taiwan The increasing trend of patterns of BZD use and its association with sleep disorders, depression, and anxiety can be used as references for stress and sleep management in nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Although the nursing professional is aware of the benefits and harms of self-medication, many allow themselves to be deceived by the idea that the medications alleviate the suffering they are going through and thus, without realizing it, they gradually increase consumption and, sometimes, switch to medications with stronger psychoactive effects. 23,25 The drugs that have higher consumption prevalence among the nursing team correspond to sedatives such as morphine and anesthetics, antidepressants, barbiturates, analgesics, amphetamines and benzodiazepines, as they are more accessible within health institutions. 15,17,19,21 Among the legal drugs, alcohol, tobacco and energy drinks are more prevalent among nurses, with higher consumption by women, with a mean age of 34 years old for alcohol abuse, 25 years old for cigarette consumption, and 24 to 49 years old for energy drinks, according to a study carried out with physicians and nurses in Bogotá.…”
Section: Predisposing Factors For the Use Of Psychoactive Substances mentioning
confidence: 99%
“…Although the nursing professional is aware of the benefits and harms of self-medication, many allow themselves to be deceived by the idea that the medications alleviate the suffering they are going through and thus, without realizing it, they gradually increase consumption and, sometimes, switch to medications with stronger psychoactive effects. 23,25 The drugs that have higher consumption prevalence among the nursing team correspond to sedatives such as morphine and anesthetics, antidepressants, barbiturates, analgesics, amphetamines and benzodiazepines, as they are more accessible within health institutions. 15,17,19,21 Among the legal drugs, alcohol, tobacco and energy drinks are more prevalent among nurses, with higher consumption by women, with a mean age of 34 years old for alcohol abuse, 25 years old for cigarette consumption, and 24 to 49 years old for energy drinks, according to a study carried out with physicians and nurses in Bogotá.…”
Section: Predisposing Factors For the Use Of Psychoactive Substances mentioning
confidence: 99%
“…Nursing has been acknowledged to be a stressful occupation with a high prevalence of distress and stress-related burnout [ 1 3 ]. The high level of occupational stress and burnout among nurses can lead to behavioral health problems and psychiatric morbidity, including insomnia [ 4 6 ], anxiety [ 7 – 10 ], depression [ 7 , 10 14 ], and substance use [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, increasing numbers of nurses in Taiwan feel frustrated and burned out in their jobs, and related behavioral health issues have drawn public attention. For example, a recent Taiwanese study reported that the patterns of occasional, frequent, and daily benzodiazepine (BZD) use among nurses exhibited an increasing trend [ 15 ]. Moreover, the risk of frequent BZD use (as opposed to infrequent BZD use) increased significantly when nurses exhibited comorbid depression, anxiety, or sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 1,097 emergency physicians, 19.96% used hypnotics; emergency physicians who used only BZDs accounted for the highest percentage, followed by those who used only non-BZDs and those who used both. Although showed an increasing trend, and those who used BZD frequently were exposed to the risk of comorbidities 29) . The results of the present study differed from those of Lan et al (2015), whose 2000-2009 analysis results revealed that 29% of the general population used hypnotics and that among those who used hypnotics, those who used a mix of hypnotics accounted for the highest percentage, followed by those who used non-BZDs and those who used BZDs 30) .…”
Section: Discussionmentioning
confidence: 99%